Hydromagnetic Flow Over a Stretching Sheet of a Viscoelastic Fluid with Uniform Suction at the Wall and Heat Transfer - Elshehawey, E.F.; Kamel, M.A.; Ibrahim, F.N. (Engineering Transactions, 1985)
A study is made for a hydromagnetic flow with heat transfer of an electrically conducting, incompressible viscoelastic fluid past a porous plate. A solution for the velocity and temperature distributions in the flow with uniform suction at the Wall is obtained. It is found that the velocities at any horizontal plane parallel to the plate in the fluid decrease as the constant magnetic field M, the variable suction parameter R and the viscoelastic parameter K increase individually keeping the other two parameters constants. It is observed that the temperature at a certain plane decreases with the increase of R, keeping K, M and the Prandtl number Pr constant. A similar effect is observed as Pr increases. However, the temperature gives a reverse relation by changing M or K. The boundary layer characteristics are estimated for different values of K, M and R.